OPTIMALISASI PENJUALAN DAN DISTRIBUSI PADA UMKM RENGGINANG CRISPY SRI REJEKI PASCA PANDEMI MELALUI JASA DELIVERY ONLINE DI WILAYAH LAMONGAN KOTA - Levia Inggrit Sayekti; Muhamad Taufik (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This situation of course greatly affects the Indonesian economy, especially the MSMEs in Lamongan City. The decrease in turnover that occurred in MSMEs was also very significant, including a decrease in business fields, namely the food and beverage sector. Online sales can be used as a strategy and means to boost economic life during a pandemic. The object of this research is the Rengginang Crispy Sri Rejeki MSME located in Geneng Hamlet near Lamongan Regency. This research aims to enable Rengginang Crispy Sri Rejeki SMEs to optimize the use of delivery services as marketing and distribution media. The method for obtaining data in the research is using a qualitative approach and conducting direct interviews with informants from the Rengginang Crispy Sri Rejeki UMKM business actors in Lamongan and also using a SWOT analysis. The results showed that sales and distribution of Rengginang Crispy Sri Rejeki through delivery services, especially local delivery in Lamongan such as cita delivery, boss delivery, and others. Collaboration between MSMEs by utilizing delivery partner services can optimize the distribution and promotion of Rengginang Crispy Sri Rejeki MSMEs so that goods can be ensured to arrive at their place and be received by consumers in intact condition.